The Wiley Blackwell anthology of African American literature - Jarrett, Gene Andrew (Wiley-Blackwell, 2014)
Includes bibliographical references and indexes; "The Wiley Blackwell Anthology of African American Literature is a comprehensive collection of poems, short stories, novellas, novels, plays, autobiographies, and essays authored by African Americans from the eighteenth century until the present. Evenly divided into two volumes, it is also the first such anthology to be conceived and published for both classroom and online education in the new millennium. Reflects the current scholarly and pedagogic structure of African American literary studies Selects literary texts according to extensive research on classroom adoptions, scholarship, and the expert opinions of leading professors Organizes literary texts according to more appropriate periods of literary history, dividing them into seven sections that accurately depict intellectual, cultural, and political movements Includes more reprints of entire works and longer selections of major works than any other anthology of its kind Works hand-in-hand with the Wiley Blackwell Companion to African American Literature, a landmark collection of essays which presents secondary criticism by eminent scholars on many texts and movements featured in the Anthology" -- Provided by publisher.